Diogenes syndrome in dementia: a case report. Issue 2 (2nd February 2021) - Sacchi, Luca; Rotondo, Emanuela; Pozzoli, Sara; Fiorentini, Alessio; Schinco, Giuseppina; Mandelli, Clara; Coppola, Carlotta; Fumagalli, Giorgio G.; Carandini, Tiziana; Pietroboni, Anna M.; Galimberti, Daniela; Triulzi, Fabio; et al.
Abstract : Background: Diogenes syndrome is a neurobehavioural syndrome characterised by domestic squalor, hoarding and lack of insight. It is an uncommon but high-mortality condition, often associated with dementia. Aims: To describe the clinical features and treatment of Diogenes syndrome secondary to behavioural variant frontotemporal dementia (bvFTD). Method: We describe a case of bvFTD in a 77-year-old man presenting with Diogenes syndrome. Results: The patient's medical and psychiatric histories were unremarkable, but in recent years he had begun packing his flat with 'art pieces'. Mental state examination revealed confabulation and more structured delusions. Neuropsychological evaluation outlined an impairment in selective attention and letter verbal fluency, but no semantic impairment, in the context of an overall preserved mental functioning. Brain magnetic resonance imaging and positron emission tomography (PET) with fluorodeoxyglucose showed mild bilateral temporo-insular atrophy and hypometabolism in the left-superior temporal gyrus respectively. An amyloid PET scan and genetic analysis covering the dementia spectrum were normal. A diagnosis of bvFTD was made. Conclusions: The clinical framing of behavioural symptoms of dementia such as hoarding poses a diagnostic challenge. This case illustrates the importance of a deeper understanding of Diogenes syndrome, leading to timelier diagnosis and effective therapeutic strategies.